The Representation of Fatherhood Identity on Netflix Cinema - M. Afifulloh (Pioneer: Journal of Language and Literature, 2022)
This study aims to investigate how a man constructs his masculinity stereotype as a father and caregiver as represented in the original Netflix’s Fatherhood. This research is qualitative with Stuart Hall's Perspectives of Representation as an approach. This perspective is to find the meaning of American fatherhood as represented in the film and to explore how the meaning of fatherhood significantly affects the global meaning of transnational communication in media. Qualitative means that a film as well as text is read from its language, image, and other aspects such as color, lighting, composition, articulation details, and role positions are taken consideration in finding meaning. The results of the study show that the fatherhood concept symbolizes ideal masculinity, anti-thesis of traditional masculinity, develops hybrid masculinity, rejects femininity as well as hegemonic masculinity, and pro-gender equality. In conclusion, the fatherhood concept inspires non-America films such as Indonesian and Indian films. This research proves that a film is made not only for economic aspects or a visual product that is intended to entertain the audience, but a film is a text that can be read, evaluated, and analyzed in depth through various approaches since a film represents a reality.